Cooperative Cation‐Binding Catalysis as an Efficient Approach for Enantioselective Friedel–Crafts Reaction of Indoles and Pyrrole. Issue 5 (6th February 2017) - Kim, Mun Jong; Xue, Lu; Liu, Yidong; Paladhi, Sushovan; Park, Si Joon; Yan, Hailong; Song, Choong Eui
Abstract: In this study, we demonstrated the cooperative cation‐binding catalysis as an efficient approach for enantioselective Friedel–Crafts reaction of indoles and pyrroles. By using highly accessible chiral oligoethylene glycol (oligoEG) as the cation‐binding catalyst and KF as the base, a highly enantioselective Friedel–Crafts reaction of indoles, 4, 7‐dihydroindoles, and pyrrole with bench‐stable α‐amidosulfones as in‐situ equivalents of sensitive imines was achieved. The scope of this new catalytic protocol was not limited to aromatic imines. Heteroaromatic and aliphatic substrates as well as α‐iminoethyl glyoxylate also afforded the desired products with excellent yields and ee s. The enforced proximity of the catalyst and substrates in a chiral cage in situ formed by incorporation of the potassium salt enhanced the reactivity and efficiently transferred the stereochemical information, mimicking the action of enzymes. Abstract :